“Backed into a Corner”: Lived experiences of receiving and providing involuntary psychiatric treatment under British Columbia’s Mental Health Act - Mary Elizabeth Snow; Amy Salmon; Jenyo Banjo; Marina Morrow; Colleen Varcoe (PLoS ONE, 2026)
British Columbia’s Mental Health Act permits the involuntarily detention and treatment of individuals who meet specific criteria. Over the past 15 years, British Columbia has seen an increasing trend in the number of involuntary psychiatric admissions. This qualitative study explores the experiences of people receiving and providing involuntary psychiatric treatment within two health organizations in British Columbia, Canada. Five focus groups were conducted with 23 individuals who had previously received involuntary psychiatric treatment at a facility operated by one of the two health organizations. All sessions were facilitated by individuals with lived experience of involuntary psychiatric treatment. Additionally, semi-structured interviews were conducted with 11 clinical staff and 10 non-clinical support personnel involved in delivering involuntary psychiatric treatment or associated services. Data were analyzed using reflexive thematic analysis, guided by an equity-oriented care framework. Seven themes were generated, including the limited availability of voluntary care options, the compounding role of social determinants of health in mental health crises, the lack of conclusive evidence supporting involuntary psychiatric treatment, the negative impacts on both patients and providers, and the importance of peer support. Across themes, participants described involuntary psychiatric care as shaped by systemic constraints with limited access to upstream, voluntary and community-based alternatives. These findings highlight the need for system-level reform to reduce reliance on coercive practices and to expand access to voluntary, community-based mental health supports that address underlying social and structural factors contributing to mental health crises.